Palladium Complexes Catalysed Telomerisation of Arylamines with Butadiene and Their Cyclisation into Quinoline Derivatives - Ramil Zaripov; Ramil Khusnitdinov; Ekaterina Ganieva; Razida Ishberdina; Kamil Khusnitdinov; Ildus Abdrakhmanov (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Since alkynyl-arylamines are widely used in the chemical industry as pre products, a method of catalytic synthesis of problematic substituted quinolines from aromatic amines containing octadienal substituents has been developed. For this purpose, the processes of N-2,7-octa-dienyl anilines cyclisation under the action of transition metal complexes and telomerisation of arylamines with butadiene in the presence of palladium complexes were studied. Suppose N-2,7-octa-dienyl anilines are synthesised by telomerisation of arylamines with butadiene in the presence of palladium complexes. In that case, the cyclisation process is carried out in the presence of catalytic amounts of Pd(II) complex with dimethyl sulfoxide or nitrobenzene. The conducted research made it possible to study the opportunity of obtaining in one stage aromatic amines substituted in the nucleus by the reaction of butadiene with arylamines in the presence of palladium complexes. The research proved the principal possibility of obtaining ortho-substituted naphthylamines from butadiene and corresponding naphthylamines in one stage. A catalytic method for the synthesis of problematic substituted quinolines in the presence of palladium complexes has been developed. It has been established that the cyclisation of N-octadienyl-arylamines into quinolines proceeds through the stage of Kleisen amino rearrangement. N-2,7-octa-dienyl anilines and their derivatives can be widely used in the paint, pharmaceutical and chemical industries. Quinoline alkenylene derivatives can be used to produce unique polymer materials, hardeners, stabilisers, extractants, sorbing agents, catalysts for the synthesis of polyurethanes, biologically active substances and their analogues. They are pre-products in synthesising alkaloids, medicines and products used in agriculture. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).